Сказка о похищенной принцессе - Биллевич Виктор Всеволодович (Новые сказочные повести, 2008)
Экземпляры: ДБ/25 (20110303) / Инвентарный номер: 46569 / Цена: 69.10 / Сис.шифр: Р2ср / Авт.знак: Б 61 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6